Writing Across the Curriculum Encounters Asynchronous Learning Networks or WAC Meets Up With ALN - Hawisher, Gail E.; Pemberton, Michael A. (Online Learning, 1997)
This paper illustrates some of the problems and successes that the authors encountered while integrating ALN into a writing across the curriculum program and an online writing lab at a large research university. Using transcripts from ALN class discussions, the authors examine students’ networked interactions and analyze the classes’ responses to a variety of online assignments in a class on English composition and pedagogy, a course on electrical and computing engineering, and a class on writing technologies. In so doing, the authors set forth several pedagogical principles which emerged from their experiences with ALN in their individual classes but which also share a number of commonalities with effective WAC practices.